Analisis Penerapan Kurikulum Merdeka dalam Pembelajaran Pendidikan Pancasila SMA Negeri 17 Surabaya - Suhartono, Suhartono; Arsana, I Wayan; Widyatama, Pandu Rudy; Fauzi, Ahkmad (Ideas Publishing, 2024)
The independent curriculum is expected to be a solution to increasing education gaps. The purpose of the study was to conduct an analysis of the implementation of the independent curriculum, information about obstacles, challenges in the implementation of the independent curriculum at SMA Negeri 17 Surabaya. The method used is descriptive qualitative, data collection is carried out by conducting interviews with subject teachers, vice principals for curriculum, and making observations. The results of the descriptive analysis that the implementation of Pancasila Education learning at SMA Negeri 17 Surabaya runs effectively and systematically, there are curricula, teaching materials, teaching media, as well as teaching methods, facilities, learning resources by considering the characteristics and needs of students. The obstacle is that there are still incomplete learning resources, not all teachers understand the application of the independent learning curriculum in learning.